Cascade DNA logic device programmed ratiometric DNA analysis and logic devices based on a fluorescent dual-signal probe of a G-quadruplex DNAzyme. Issue 19 (16th February 2016) - Fan, Daoqing; Zhu, Jinbo; Zhai, Qingfeng; Wang, Erkang; Dong, Shaojun
Abstract : Two fluorescence sensitive substrates of G4 DNAzyme with inverse responses were simultaneously used to a cascade advanced DNA logic device based DNA analysis for the first time. Abstract : Herein, two fluorescence sensitive substrates of G-quadruplex/hemin DNAzyme with inverse responses (Scopoletin and Amplex Red) were simultaneously used in one homogeneous system to construct a cascade advanced DNA logic device for the first time (a functional logic device (a three input based DNA calliper) cascade with an advanced non-arithmetic logic gate (1 to 2 decoder)). This cascade logic device was applied to label-free ratiometric target DNA detection and length measurement.